Carbon-coated cobalt molybdenum oxide as a high-performance electrocatalyst for hydrogen evolution reaction. (27th December 2018) - Xu, Ning; Cao, Guoxuan; Gan, Liyong; Chen, Zhengjun; Zang, Mingjie; Wu, Hui; Wang, Ping
Abstract: Synthesis of high-performance and cost-effective catalysts towards the hydrogen evolution reaction (HER) is critical in developing electrochemical water-splitting as a viable energy conversion technique. For non-precious metal Co- and Ni-based catalysts, hydroxides were found to form on the surface of the catalysts under alkaline environments and benefit the catalytic performance, whereas there is limited systematic study on the explicit influence of hydroxides on the electrocatalytic mechanism and performance of these catalysts. Herein, we report a close correlation observed between the amount of the surface hydroxides formed and the resulting electrocatalytic performance of a Co-Mo-O nanocatalyst through careful comprehensive structural and property characterizations. We found that an appropriate amount of hydroxide can be moderated by simply coating the catalyst surface with carbon shells to optimize the catalytic properties. As a result, a carbon-coated Co-Mo-O nanocatalyst was successfully developed and is among the best reported non-precious HER catalysts with a superior electrocatalytic activity and outstanding durability for the HER under alkaline environment. First-principles calculations were further conducted to probe the nature of the active sites and the role of hydroxides in the Co-Mo-O@C/NF catalyst towards the HER. Highlights: A carbon-coated Co-Mo-O@C/NF nanocatalyst was successfully synthesized. Coating carbon on the catalyst can moderate the growth of Co(OH)2 nanoplates. The catalyst exhibited excellent activity and outstanding stability toward HER.